1978
DOI: 10.1073/pnas.75.2.686
|View full text |Cite
|
Sign up to set email alerts
|

Preferential transcription of the ovalbumin gene in isolated hen oviduct nuclei by RNA polymerase B.

Abstract: The synthesis of ovalbumin mRNA sequences was studied in isolated nuclei from hen oviduct. Two different methods of analysis were used to distinguish in vitro synthesized from preexisting mRNA sequences: (i) Mercurated ribonucleotides were used for in vitro RNA synthesis, and the newly synthesized RNA was purified by chromatography on sulfhydrylagarose and hybridized to radioactive ovalbumin cDNA. (ii) (3HJUTP was used to label the in vitro synthesized RNA. Hybridization to unlabeled mercurated cDNA, RNase A d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0

Year Published

1979
1979
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 34 publications
(26 reference statements)
1
19
0
Order By: Relevance
“…of HzO, adjusted to 0.5 "/, sodium dodecyl sulfate, and digested with proteinase K (10 mg/ml) at 37°C for 1 h. The nucleic acids were extracted by the hot phenol method [13], and passed through a column of SephadexG-75 in 10 mM Tris/HCl, pH 7.5, containing 1 mM EDTA. The mercurated RNA, synthesized in vitro, was separated from endogenous nuclear RNA by affinity chromatography on a sulfhydryl-Sepharose column (Servachrom A-SH), in the presence of formamide, as described by Nguyen-Huu et al [14].…”
Section: Isolation and Sizing Of The Rna Synthesized In Vitromentioning
confidence: 99%
“…of HzO, adjusted to 0.5 "/, sodium dodecyl sulfate, and digested with proteinase K (10 mg/ml) at 37°C for 1 h. The nucleic acids were extracted by the hot phenol method [13], and passed through a column of SephadexG-75 in 10 mM Tris/HCl, pH 7.5, containing 1 mM EDTA. The mercurated RNA, synthesized in vitro, was separated from endogenous nuclear RNA by affinity chromatography on a sulfhydryl-Sepharose column (Servachrom A-SH), in the presence of formamide, as described by Nguyen-Huu et al [14].…”
Section: Isolation and Sizing Of The Rna Synthesized In Vitromentioning
confidence: 99%
“…Injections of estrogen into chickens that had been prestimulated with estrogen and then withdrawn from all hormone (secondary stimulation) induced the accumulation of ovalbumin mRNA (mRNAOv) (4)(5)(6)(7). Recently, it has been shown that the structural sequences of the ovalbumin gene (8)(9)(10) and globin gene are interrupted by multiple regions of nonstructural intervening sequences.…”
mentioning
confidence: 99%
“…Since the cytoplasm is absent from the nuclei in the in vitro system one can control the nuclear environment precisely and in particular for the screening of putative cytoplasmic regulatory molecules. In addition, nuclei incubated in vitro have been shown to add poly(A) tails (7,14,15), initiate RNA synthesis (2,3,6,9,13,14), produce discrete RNA sequences (2,8,10,(11)(12)(13), and process precursor mRNA (15).…”
Section: Introductionmentioning
confidence: 99%
“…We have previously shown that the chicken liver nuclei were able to reinitiate RNA synthesis in vitro (2). RNA synthesis in isolated purified nuclei has been described for a large number of different cell types (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15), but in all cases the endogenous DNA was used as the sole source of template. Since the cytoplasm is absent from the nuclei in the in vitro system one can control the nuclear environment precisely and in particular for the screening of putative cytoplasmic regulatory molecules.…”
mentioning
confidence: 99%